2021
DOI: 10.4103/jmu.jmu_47_20
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Assessment of Some Abdominal Organs in Children with Sickle Cell Disease in Ilorin, Nigeria

Abstract: Background: The irregular sickle cells can block blood vessels, causing tissue and organ damage and in most cases presented with pain as a result of organ ischemia. Ultrasonography is an easily available instrument for investigating abdominal organs which are most commonly affected by sickle cell disease (SCD). This study was aimed to assessing liver, gall bladder, spleen, and kidney in children with SCD in Ilorin, Kwara State. Methods: A prospective cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
0
2
Order By: Relevance
“…While only a limited number of abdominal imaging was performed in our cohort (33% for abdominal radio- SCD in Turkey, Nigeria, and Greece, respectively. 28,30,31 In contrast to our study, which revealed gallbladder abnormalities as the most common abdominal US imaging abnormality, these studies showed hepatomegaly was the most common abnormality found on abdominal US. It is likely that the difference in their results and ours could be because we evaluated imaging abnormalities only in patients with a complaint of abdominal pain.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…While only a limited number of abdominal imaging was performed in our cohort (33% for abdominal radio- SCD in Turkey, Nigeria, and Greece, respectively. 28,30,31 In contrast to our study, which revealed gallbladder abnormalities as the most common abdominal US imaging abnormality, these studies showed hepatomegaly was the most common abnormality found on abdominal US. It is likely that the difference in their results and ours could be because we evaluated imaging abnormalities only in patients with a complaint of abdominal pain.…”
Section: Discussioncontrasting
confidence: 93%
“…Balci et al., Muftaudeen et al., and Papadaki et al. also reported high prevalence solid organ abnormalities on abdominal US in their patients with SCD in Turkey, Nigeria, and Greece, respectively 28,30,31 . In contrast to our study, which revealed gallbladder abnormalities as the most common abdominal US imaging abnormality, these studies showed hepatomegaly was the most common abnormality found on abdominal US.…”
Section: Discussioncontrasting
confidence: 87%